Investigation of structural, vibrational and ferroic properties of AgNbO3 at room temperature using neutron diffraction, Raman scattering and density-functional theory. (6th June 2015) - Niranjan, Manish K; Ganga Prasad, K; Asthana, Saket; Rayaprol, S; Siruguri, V
Abstract We perform a comprehensive study of the structural, lattice dynamical and ferroic properties of the room temperature phase of AgNbO3 using a combination of neutron diffraction, Raman spectroscopy and first-principles density functional theory. The Rietveld analysis of neutron diffraction data indicates that AgNbO3 at room temperature crystallizes in an orthorombic structure with noncentrosymmetric Pmc21 space group symmetry. The zone-center phonon mode frequencies of Pmc21 and Pbcm phases of AgNbO3 are computed and are found to be in good agreement with experimentally obtained Raman mode frequencies. Computed frequencies for both space groups are found to be very close. However, computed modes with frequencies 488 and 846 cm−1 are found to be Raman-active for the Pmc21 phase while Raman inactive for Pbcm phase. The computed potential energy surfaces and Born effective charges of the ions suggest that the primary contribution to ferroic properties of AgNbO3 come from Nb and O ions only. Furthermore the calculated potential energy profiles suggest competing ferroic and antiferrodistortive instabilities in AgNbO3 are primarily due to the off-centering of Nb ions and rotations of NbO6 octahedra, respectively.